An optimistic outlook on the use of evidence syntheses to inform environmental decision‐making. Issue 6 (5th April 2021) - Thomas‐Walters, Laura; Nyboer, Elizabeth A.; Taylor, Jessica J.; Rytwinski, Trina; Lane, John F.; Young, Nathan; Bennett, Joseph R.; Nguyen, Vivian M.; Harron, Nathan; Aitken, Susan M.; Auld, Graeme; Browne, David; et al.
Abstract: Practitioners and policymakers working in environmental arenas make decisions that can have large impacts on ecosystems. Basing such decisions on high‐quality evidence about the effectiveness of different interventions can often maximize the success of policy and management. Accordingly, it is vital to understand how environmental professionals working at the science‐policy interface view and use different types of evidence, including evidence syntheses that collate and summarize available knowledge on a specific topic to save time for decision‐makers. We interviewed 84 senior environmental professionals in Canada working at the science‐policy interface to explore their confidence in, and use of, evidence syntheses within their organizations. Interviewees value evidence syntheses because they increase confidence in decision‐making, particularly for high‐profile or risky decisions. Despite this enthusiasm, the apparent lack of available syntheses for many environmental issues means that use can be limited and tends to be opportunistic. Our research suggests that if relevant, high quality evidence syntheses exist, they are likely to be used and embraced in decision‐making spheres. Therefore, efforts to increase capacity for conducting evidence syntheses within government agencies and/or funding such activities by external bodies have the potential to enable evidence‐based decision‐making.